The Effect of Accounting Literacy, GPA Score, and Spiritual Quotient on Academic Fraud of Accounting Students : Study on Accounting Student of the Bina Darma University - Tania Tania; Muhammad Titan Terzaghi; Dewi Sartika (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Academic fraud undermines educational quality and threatens the professional integrity of future accountants. This study examines the effects of accounting literacy, grade point average (GPA), and spiritual quotient on academic fraud among accounting students at Bina Darma University, Palembang, Indonesia. A quantitative survey design was employed, involving 91 active students, and the data were analysed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that accounting literacy has a positive but statistically insignificant relationship with academic fraud, while spiritual quotient shows a negative but insignificant effect. In contrast, GPA has a significant positive effect, suggesting that stronger academic performance may coincide with greater pressure to maintain achievement and, consequently, a higher risk of dishonest behaviour. The model explains a substantial proportion of the variance in academic fraud. These findings highlight academic performance pressure as a central determinant of misconduct and suggest that universities should complement academic achievement policies with integrity education, ethical supervision, and preventive mechanisms that reduce incentives for dishonest practices.